Stages in the psychological resolution of schizophrenia - Steggles, Gillian R. M. (Frontiers in Psychology, 2015)
From the work of Dr. Michael Robbins in Massachusetts, USA, it is known that 9 schizophrenic patients out of a series of 18, and a further schizophrenic patient, treated by him achieved positive outcomes using psychoanalytic methodology. Four of these had strikingly successful outcomes, for example completing their treatment without a need for further medication, and also becoming happily married or graduating at university. This paper aims to illustrate the stages identified by him through which this can be accomplished. Dr. Robbins' Stages of Psychological Therapy of Schizophrenia are compared with Dr. Steggles' detailed case study of a patient's recovery from schizoaffective disorder. These two data sources are juxtaposed and compared. Dr. Robbins' therapeutic stages are found to parallel exactly Dr. Steggles' findings from her case study, which she summarized as her PPCC (Psychodynamic Pentapointed Cognitive Construct) model of her schizoaffective patient's experience. Psychological therapy of schizophrenia is still in its early stages of development. However, Dr. Robbins' psychoanalytic psychotherapy technique has given rise to positive outcomes in 10 out of 19 patients he treated.